A reporter cell line for the automated quantification of SARS-CoV-2 infection in living cells - Desmarets, Lowiese; Callens, Nathalie; Hoffmann, Eik; Danneels, Adeline; Lavie, Muriel; Couturier, Cyril; Dubuisson, Jean; Belouzard, Sandrine; Rouillé, Yves (Frontiers in Microbiology, 2022)
The SARS-CoV-2 pandemic and the urgent need for massive antiviral testing highlighted the lack of a good cell-based assay that allowed for a fast, automated screening of antivirals in high-throughput content with minimal handling requirements in a BSL-3 environment. The present paper describes the construction of a green fluorescent substrate that, upon cleavage by the SARS-CoV-2 main protease, re-localizes from the cytoplasm in non-infected cells to the nucleus in infected cells. The construction was stably expressed, together with a red fluorescent nuclear marker, in a highly susceptible clone derived from Vero-81 cells. With this fluorescent reporter cell line, named F1G-red, SARS-CoV-2 infection can be scored automatically in living cells by comparing the patterns of green and red fluorescence signals acquired by automated confocal microscopy in a 384-well plate format. We show the F1G-red system is sensitive to several SARS-CoV-2 variants of concern and that it can be used to assess antiviral activities of compounds in dose-response experiments. This high-throughput system will provide a reliable tool for antiviral screening against SARS-CoV-2.